Using the technologies of the cooperative teaching during laboratory employments of natural (to zoology) at higher school (Pedagogy of Higher and Secondary Education, 2013)
Lysogor L. P. Using the technologies of the cooperative teaching during laboratory employments of natural (to zoology) at higher school.The article considers the problems of using the technology of cooperative teaching during laboratory employments on zoology which will influence the choice to achieve high results in mastering knowledge of zoology.
Keywords: innovative methods of teaching; creative capabilities; cooperative teaching; teaching-collaboration